Optimised limit for polarimetric calibration of fully polarised SAR systems. Issue 9 (4th April 2016) - Chen, Jie; Guo, Wei; Li, Zhuo; Liu, Wei
Abstract : The optimised limit for polarimetric calibration of fully polarised synthetic aperture radar systems is derived by establishing an error model as a function of cross‐talk, channel imbalance and system noise. Compared with noise equivalent sigma zero, the polarimetric error below the optimised limit is too small to affect the signal of cross‐polarised channel. Thus, polarimetric calibration could be relaxed or even ignored in this case. With the backscatter model, optimised limits for cross‐talk and channel imbalance at X, C and L‐bands are presented. Moreover, when ignoring channel imbalance, the limit for cross‐talk is given in a quantitative way. These results are very useful in practice, allowing significant reduction in calibration cost.